Comparison of flexoelectric and piezoelectric ring energy harvester. (June 2019) - Zhang, XF; Hu, KM; Li, H
Flexoelectric/piezoelectric effect is an electromechanical coupling effect occurring in dielectrics. In this study, a flexoelectric/piezoelectric ring energy harvester is proposed based on the direct flexoelectric/piezoelectric effect. The flexoelectric/piezoelectric ring energy harvester is made of an elastic ring and a flexoelectric/piezoelectric patch laminated on its surface. The electromechanical coupling mechanism of the flexoelectric/piezoelectric ring energy harvester is explored. Then the voltage and power output across the load resistance are derived in the closed-circuit condition for the energy harvester. The distinctive characteristics between the flexoelectric and the piezoelectric energy harvesters are discussed and compared in detail. The output power/voltage is related to various parameters, such as flexoelectric/piezoelectric patch size, load resistance, and flexoelectric/piezoelectric patch thickness, which are discussed to improve the power output across the load resistance. The flexoelectric ring energy harvester is more effective than the piezoelectric ring energy harvester in the transverse oscillation-bending dominant vibration, since the flexoelectric effect is sensitive to the strain gradient (bending strain). This study, including theoretical derivations and simulation plots, provide design guidelines in engineering applications for flexoelectric/piezoelectric effect.